2017
DOI: 10.3390/w9070472
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Agricultural Wetland-Reservoir-Irrigation Management System

Abstract: Constructed wetlands (CW) have gained recognition as a management option for the treatment of various agricultural wastewaters. This study involved the design, construction, and initial evaluation of a wetland-reservoir-irrigation (WRI) system. The system was established in Truro, Nova Scotia, Canada, with the goal to capture, treat, and re-use agricultural sub-surface drainage water. It consisted of a 1.8-ha area of a cropped field that was systematically tile drained. Drainage water was directed through a 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
3
2
Order By: Relevance
“…If single years are analysed, the retention was only 40% in 2018. This value was lower than 68% reported by Haverstock et al (2017), most probably due to the lower HRT. In fact, the average HRT during the Event 1, that represented 76% of the total yearly inflow, was 6.6 days (Table 3), while for the system studied by Haverstock et al it was 15 days.…”
Section: Water Qualitycontrasting
confidence: 75%
See 2 more Smart Citations
“…If single years are analysed, the retention was only 40% in 2018. This value was lower than 68% reported by Haverstock et al (2017), most probably due to the lower HRT. In fact, the average HRT during the Event 1, that represented 76% of the total yearly inflow, was 6.6 days (Table 3), while for the system studied by Haverstock et al it was 15 days.…”
Section: Water Qualitycontrasting
confidence: 75%
“…Like other types of naturebased solutions, SFCWs used for agricultural drainage water treatment are being used at different scales, for different catchments and in different climates, and that makes comparison among them rather difficult. In this study, the average water inflow (61 m 3 day -1 in 2018 and 27 m 3 day -1 in 2019) was much lower than the one given by Dal Ferro et al (2018) for a SFCW in the Veneto region (Italy) that approximately amounted to 5,480 m 3 day -1 , but was also much higher than 17 m 3 day -1 for a Canadian SFCW studied by Haverstock et al (2017).…”
Section: Simplified Overall Water Balancecontrasting
confidence: 60%
See 1 more Smart Citation
“…Constructed wetlands have been used to improve water quality delivered from cropland via two predominant pathways: surface flows (e.g., precipitation-driven runoff or irrigation tailwaters) or subsurface drainage (e.g., tile drainage). Table 1 summarizes the data compiled from 39 scholarly papers (28 surface-flow influent sources and 11 subsurface drainage influent sources), representing studies conducted on three continents (North America, Europe, Asia) and published between the years 2000 and 2019 (Bass, 2000;Beutel et al, 2014;Blankenberg et al, 2016;Borin and Tocchetto, 2007;Braskerud, 2002;Chen et al, 2015;Díaz et al, 2012;Dunne et al, 2015;Fink and Mitsch, 2004;Goddard and Elder, 1997;Gu, 2008;Han et al, 2017;Haverstock et al, 2017;Hoagland et al, 2001;Hoffmann et al, 2012;Juston and DeBusk, 2006;Kasak et al, 2018;Kim et al, 2010;Koskiaho et al, 2003;Kovacic et al, 2000Kovacic et al, , 2006Larson et al, 2000;Lavrnić et al, 2018;Lentz et al, 2014;Liikanen et al, 2004;Lu et al, 2009;Ludwig, 2010;Maniquiz et al, 2012;Maxwell et al, 2017;Miller et al, 2002;Moreno-Mateos et al, 2009;Mustafa et al, 2009;Pietro and Ivanoff, 2015;Poe et al, 2003;Rei...…”
Section: Constructed Wetlands For Croplandmentioning
confidence: 99%
“…Our result found that hydrologic, human, and climatic factors accounted for conversions to farmland appropriately. Sufficient hydrologic conditions provided water protection for agricultural irrigation and plant growth [ 100 , 101 ]. The higher temperature in the south promoted the evaporation of swamps water and provided proper climatic conditions for crop growth in cold temperature regions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%